Constitution, objects and proceedings of the Financial Reform Association [electronic resource] : the Hudson's Bay monopoly. - Financial Reform Association (Liverpool, Merseyside) (Liverpool : The Association; London : P.S. King, 1858)
At head of title: Financial Reform Tracts. "New Series, No. XXIV.]" "[Conclusion." Electronic reproduction. Mode of access: Internet. 44